2001
DOI: 10.1097/00000658-200106000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant Chemoradiation for Rectal Cancer: Analysis of Clinical Outcomes From a 13-Year Institutional Experience

Abstract: ObjectiveTo examine clinical outcomes in patients receiving neoadjuvant chemoradiation for locally advanced rectal adenocarcinoma. Summary Background DataPreoperative radiation therapy, either alone or in combination with 5-fluorouracil-based chemotherapy, has proven both safe and effective in the treatment of rectal cancer. However, data are lacking regarding which subgroups of patients benefit from the therapy in terms of decreased local recurrence and increased survival rates. MethodsA retrospective chart r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
77
2
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(87 citation statements)
references
References 39 publications
6
77
2
2
Order By: Relevance
“…In our study, over 40% of patients had T4 tumours representing a group of patients with truly locally advanced disease. This may account for the low pathological complete response rate seen in our study compared with 10 -30% achieved in other studies (Janjan et al, 1999;Bosset et al, 2000;Chan et al, 2000;Grann et al, 2001;Onaitis et al, 2001;Valentini et al, 2001). Two studies included only patients with clinically staged T4 tumours (Videtic et al, 1998;Rodel et al, 2000).…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…In our study, over 40% of patients had T4 tumours representing a group of patients with truly locally advanced disease. This may account for the low pathological complete response rate seen in our study compared with 10 -30% achieved in other studies (Janjan et al, 1999;Bosset et al, 2000;Chan et al, 2000;Grann et al, 2001;Onaitis et al, 2001;Valentini et al, 2001). Two studies included only patients with clinically staged T4 tumours (Videtic et al, 1998;Rodel et al, 2000).…”
Section: Discussionmentioning
confidence: 54%
“…Many recent studies included T3 tumours staged by endoscopic ultrasound which are often less bulky than clinically staged T3 tumours. Very few patients with T4 tumours were recruited (o5% of total enrolled) in these studies (Janjan et al, 1999;Bosset et al, 2000;Chan et al, 2000;Grann et al, 2001;Onaitis et al, 2001;Valentini et al, 2001). In our study, over 40% of patients had T4 tumours representing a group of patients with truly locally advanced disease.…”
Section: Discussionmentioning
confidence: 99%
“…pCR rates following preoperative CRT are shown in a body of research literature to range from 9% to 30% (1,2,7,8,10,11,15,16) while some studies report a partial response to neoadjuvant treatment of 51% (6,11). The correlation between response to neoadjuvant treatment and oncologic outcome has been reported in other studies (3,4,(6)(7)(8)(9)(10)(11)(12)(17)(18)(19)(20)(21)(22)(23).…”
Section: Discussionmentioning
confidence: 90%
“…Neoadjuvant treatment can lead to a significant downstaging of colorectal tumours and this may in part explain the difference in T stage between groups [36,37]. Nevertheless two randomised trials have shown that preoperative chemoradiotherapy does not increase postoperative complications.…”
Section: Discussionmentioning
confidence: 99%